Partial anomalous systemic venous drainage, right superior vena cava to the left atrium in nonisomeric patient - Salem Deraz; Olfat Alzaabi; Anshad Ummerkhan; Sidra Abdul Hakeem; Hamza Elnady; Ahmed Al Kamali (Wolters Kluwer Medknow Publications, 2023)
The most encountered anomalous systemic venous drainage is a persistent left superior vena cava that drains into the right atrium through the coronary sinus. A much rarer anomalous systemic venous drainage is that of isolated anomalous drainage of a normally positioned right superior vena cava (RSVC) into the left atrium (LA). This has been reported in approximately 20 patients, with the diagnosis usually made by cardiac catheterization. We report the youngest case diagnosed at the age of 3 h after birth with hypoxemia resulting from anomalous drainage of a normal RSVC into the LA. This was diagnosed noninvasively by echocardiography and confirmed by cardiac computed tomography angiography.